Living on your own terms : what is real rebellion? - Osho. (b)
Forty years after the rebellions of the 1960s a new generation is again in the streets to challenge and to rebel against outdated structures and values, focusing political and economic systems and their failings. This book intends to support this new generation. It focuses on the most important questions in the life of the individual.
Keywords: Spiritual life -- Osho International Foundation; Conduct of life